Inclusive early childhood development in Nepal: The impact of teacher training, parental involvement, and accessibility on children with disabilities - Chouhan, Tara (Damak Campus Journal, 2025)
This study investigates the influence of teacher training, parental involvement, and geographic accessibility on the developmental outcomes and enrollment rates of children in Nepal’s Early Childhood Development (ECD) system, with particular attention to inclusive education for children with disabilities. Employing a mixed-methods approach, data were collected through structured surveys, standardized developmental assessments, GPS-enabled measurements of distance to ECD centers, and key informant interviews involving 150 participants, including educators, parents, and children from diverse regions. Quantitative analyses using correlation, multiple linear regression, and logistic regression revealed strong positive associations between teacher training and parental involvement with child developmental scores and enrollment likelihood. Conversely, increased distance from ECD centers significantly reduced both developmental outcomes and enrollment rates. Specifically, teacher training was strongly correlated with improved child development (r = 0.72, p < 0.01) and parental involvement showed a similar positive relationship (r = 0.67, p < 0.01). Distance exhibited a negative correlation (r = -0.70, p < 0.01), indicating barriers to access. Regression models confirmed these predictors explained 75% of variance in developmental scores (R2 = 0.75, p < 0.001). Logistic regression showed each additional kilometer from an ECD center decreased enrollment odds by 35%, while higher parental involvement increased enrollment odds by 40%. Teacher training had a modest effect on enrollment (3% increase per unit). These findings emphasize the need for multi-faceted interventions including enhanced professional development for ECD teachers, strategies to foster active parental engagement, and targeted efforts to reduce geographic barriers. Recommendations include expanding inclusive teacher training programs, strengthening family involvement through community outreach, and increasing accessibility by establishing additional centers, mobile services, and transportation support. This comprehensive approach is critical for improving both access to and quality of early childhood education in Nepal, particularly for children with disabilities, thereby promoting equitable developmental opportunities and educational inclusion.